1978
DOI: 10.1017/s0021859600056185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of severe food restriction on growth rate, muscle distribution and muscle: bone ratio in pigs

Abstract: In a previous experiment we investigated the effects of a restricted intake of dietary energy, protein or both on carcass anatomy in pigs (Carden & Goenaga, 1977). Contrary to results of Elsley, McDonald & Fowler (1964) and of Richmond & Berg (1971) we found several changes in muscle distribution, which gave rise to differences in the proportion of the commercially valuable muscles in the carcasses. The treatments had no effect on an important trait, the muscle: bone ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In any case, these results are contrary to the trend shown for each of males, castrates and females, by Davies et al (1980) where the fastergrowing pigs had the higher muscle:bone ratio. Elsley et al (1964), Goenaga & Carden (1978) and Walstra (1980) found negligible differences in muscle:bone ratio with differences in growth rate due to nutrition.…”
Section: The Nutritional Effect On the Muscle: Bone Ratiomentioning
confidence: 97%
“…In any case, these results are contrary to the trend shown for each of males, castrates and females, by Davies et al (1980) where the fastergrowing pigs had the higher muscle:bone ratio. Elsley et al (1964), Goenaga & Carden (1978) and Walstra (1980) found negligible differences in muscle:bone ratio with differences in growth rate due to nutrition.…”
Section: The Nutritional Effect On the Muscle: Bone Ratiomentioning
confidence: 97%